Arabinogalactan and fructooligosaccharides improve the gut barrier function in distinct areas of the colon in the Simulator of the Human Intestinal Microbial Ecosystem. (January 2016) - Daguet, David; Pinheiro, Iris; Verhelst, An; Possemiers, Sam; Marzorati, Massimo
Highlights: AG and FOS have a different fermentation profile in the colon. Both fibres can modulate the gut wall functionality in their area of fermentation. In vitro fibre fermentation is linked to increased TEER. In vitro fibre fermentation is linked to decreased pro-inflammatory cytokine. Abstract: Impaired gut epithelium functionalities coupled with microbial dysbiosis contribute to the development of diseases such as inflammatory bowel disease (IBD). Functional foods represent an interesting possibility to modulate the gut microbiota and hence the gut barrier functionality. The effect of arabinogalactan (AG) and fructooligosaccharides (FOS) has been studied in a Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) – inoculated with faecal material from an IBD patient – coupled with co-cultures of enterocyte-like cells (Caco-2) and macrophages (THP1). AG and FOS showed a different fermentation profile in the colon (proximal for FOS, distal for AG) and both fibres exerted a potential positive effect on gut barrier and inflammation. AG showed a significantly higher transepithelial electrical resistance of Caco-2 cells, decreased NF-κB activity and increased IL-10 production. These results suggest that AG could be an interesting supplement for those conditions characterized by inflammation and increased permeability in the distal colon.